Long-Term Survival of Patients With Chemotherapy-Naïve Metastatic Nasopharyngeal Carcinoma Receiving Cetuximab Plus Docetaxel and Cisplatin Regimen - Zhang, Mengping; Huang, He; Li, Xueying; Huang, Ying; Chen, Chunyan; Fang, Xiaojie; Wang, Zhao; Guo, Chengcheng; Lam, Sioteng; Fu, Xiaohong; Hong, Huangming; Tian, Ying; et al. (Frontiers in Oncology, 2020)
Purpose: Metastatic nasopharyngeal carcinoma (mNPC) remains incurable. This prospective study aimed to investigate whether adding cetuximab to cisplatin-based induction therapy could improve efficacy and survival for chemotherapy-naïve mNPC patients. Patients and methods: Eligible chemotherapy-naïve mNPC patients were enrolled, including those initially diagnosed with mNPC (IM) and those with first-relapse metastases after radiotherapy (RM). Patients all received induction chemotherapy (IC) including docetaxel and cisplatin plus cetuximab. Those who obtained objective remission after IC would continue to receive radiotherapy concurrent with cetuximab and cisplatin, and further capecitabine as maintenance. Contemporaneous patients who received conventional therapy served as controls. Results: Forty-three patients were enrolled, including 17 IM and 26 RM patients. Thirty-nine (90.7%) patients had WHO III subtype. The overall response and complete response (CR) rates were, respectively, 79.1% and 34.9% after induction therapy and 76.7% and 46.5% after chemoradiotherapy. The 5-year overall survival (OS) and progression-free survival (PFS) rates reached 34.9% and 30%, respectively. Subgroup analysis showed that compared with RM patients, IM patients had a higher 5-year OS (58.8% vs. 19.2%) and PFS (52.9% vs. 19.2%). The IM group had a higher CR rate of induction treatment than the RM group (52.9% vs. 23.1%). No treatment-related death was observed. Twelve patients (27.9%) remained alive with disease-free survival times from 60+ to 135+ months. Control patients showed a substantially lower survival rate (5-year OS, 10.9%) and few long-term survivors. Conclusions: This regimen resulted in significantly improved efficacy and survival, which indicates a potentially curative role for chemotherapy-naïve mNPC, especially in newly diagnosed patients. A phase III clinical trial (NCT02633176) is ongoing for confirmation.